A rare case of gastrointestinal stromal tumor presenting with closed perforation of the small intestine - Ahat ANDİCAN and Fahri GÖKÇAL and Afag AGAYEVA and Fatih GÜLŞEN and Ferhat ÖZDEN and Volkan ÖZBEN (Turkish Journal of Gastroenterology, 2019)
-